Exploring how personal mentoring added value to becoming a higher education practitioner - Makhanya, S.G. (South African Journal of Higher Education, 2018)
I explore personal mentoring that I received on my journey to becoming an experienced higher education practitioner. The context of my personal mentoring was the community where I was born and grew up. I used a bricolage research approach by combining autoethnography and personal history research methodologies. Living theory enabled me to understand how values from my personal mentors have influenced my professional development and practice. I nominated my father, mother, community members, maternal and paternal grandmothers as my personal mentors. I generated data by working with artefacts in the form of photographs and an object. Writing a personal history narrative and reflecting made visible values learned from personal mentoring, which were motivation, kindness, care and selflessness. These values learned from interacting with my family and community members made a significant contribution to my becoming an experienced higher education practitioner.